STRATEGI GURU AL-QUR'AN HADIS DALAM MENGATASI KENDALA PEMBELAJARAN MEMBACA AL-QUR'AN PADA SISWA MI MUHAMMADIYAH PAGERKIDUL - Yuni Astuti Munawaroh (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
This study aims to describe the strategies applied by Al-Qur'an Hadith teachers in overcoming the obstacles of learning to read the Qur'an in students at MI Muhammadiyah Pagerkidul. Learning to read the Qur'an is a fumdamental aspect in Islamic religious education which is often faced with various obstacles such as low ability of students to recognize hijaiyah letters and weak understanding of tajweed. This study uses a qualitative descriptive approach with data collection techniques through observation and interviews. The results of the study show the importance of the role of teachers as facilitators in applying innovative methods such as Iqra', Wafa, and Tartil to help students overcome difficulties in reading. In addition, parental involvement in supporting the learning process at home is also a crucial factor. With the implementation of various appropriate strategies, it is hoped that students will not only be able to read the Qur'an well, but also understand and practice Islamic teachings more deeply.